The Role of Cloud Computing in Accelerating Small and Medium Enterprise Growth - Rudi Santoso; Andi Pratama (Digital Innovation : International Journal of Management, 2024)
This article explores how cloud computing solutions enhance operational efficiency, scalability, and cost-effectiveness in small and medium enterprises (SMEs). By examining case studies from various industries, the research highlights the transformative role of cloud platforms in driving innovation, improving collaboration, and expanding market reach. The findings underscore the potential of cloud technologies in accelerating SME growth, while also addressing challenges such as adoption costs, technical expertise, and data security concerns.